Implementasi Dharma Dakwah Islamiyah Dalam Mewujudkan Universitas Islam Riau Sebagai Kampus Madani - Harahap, Musaddad (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
This research problem relates to private higher education institutions which are nomenclature under the supervision of the Ministry of Education, Culture, Research, and Technology through LLDIKTI. This model institution in the national discourse is identical to the General Higher Education institution (PTU). Meanwhile, if examined into the institution, it is found that the basic concept is Islam. The institution in question is the Islamic University of Riau. Islamic University of Riau itself is categorized as a PTU institution, on the other hand, this institution is also characterized by Islam. The method used in this research is qualitative with a phenomenological approach. Data collection is focused on social situations consisting of places, actors, and activities that interact synergistically. Meanwhile, the data analysis used consisted of data reduction, data display, and conclusion drawing/verification. The results of this study are the Islamic University of Riau is a higher education institution based on Islam. Although by regulation it is considered a Public Higher Education (PTU), the Islamic University of Riau remains consistent with the basic idea of ​​its establishment. Meanwhile, the implementation of chess dharma da'wah Islamiyah in realizing a civil society campus at the Islamic University of Riau has been well programmed and carried out consistently in various existing units. The Islamic da'wah model is carried out by providing Islamic guidance for all academics. With good Islamic coaching, a good understanding of Islam is formed, so that all academics have the awareness to play a role in Islamic da'wah.